Short duration exhaustive aerobic exercise induces oxidative stress: a novel play-oriented volitional fatigue test - Kyparos, A.; Salonikidis, K.; Nikolaidis, M. G.; Kouretas, D. (The Journal of Sports Medicine and Physical Fitness, 2007)
Aim: Exercise is associated with the generation of reactive oxygen and nitrogen species. This study examined the oxidative stress in response to a novel volitional fatigue test. Methods: Eleven male college students performed a volitional fatigue test consisting of shuttle runs with a tennis racquet in the hand towards the left and right sidelines within the tennis singles court in an attempt to hit tennis balls until exhaustion. A tennis ball serving machine was adjusted to alternate feeds to the forehand and backhand sides of the subjects, standing at the baseline, at a frequency of 20 balls per minute. Results: Mean time to volitional fatigue was 5.9±1.3 min and mean heart rate at volitional fatigue was 189±8.1 beats/min. The volitional fatigue test resulted in significant increases in blood thiobarbituric acid-reactive substances (22%), protein carbonyls (58%), catalase activity (143%), total antioxidant capacity (34%) and oxidized glutathione (GSSG, 81%) concentration, as well as significant decreases in reduced glutathione (GSH, 15%) concentration and GSH/GSSG ratio (56%) immediately postexercise, as compared to the pre-exercise concentration. Conclusion: The data provide evidence that acute short duration exhaustive aerobic exercise in the form of a novel volitional fatigue test is capable of inducing oxidative stress. This novel test could serve as an alternative exercise modality to study oxidative stress.